Forbidden promises - Robert, Katee (Robert, Katee. O'Malleys series., 2017)
Sloan O'Malley just left her entire world behind-her family, her wealth, and even her real name. For the first time in her life, she's free. She can live the "normal" life she's always wanted. A life without fear. But there's nothing safe about her intensely sexy next-door neighbor. Jude MacNamara has no room for innocence in his life. Only revenge. Still, he's never been able to walk away from the forbidden, and Sloan-who is every inch of pure, mouthwatering temptation-has forbidden written all over her. Only after it's way too late does he discover the real danger: claiming Sloan as his puts a target on her back. To protect her, Jude is willing risk everything . . . and to hell with the consequences.